Flexible resistive random access memory and preparation method thereof

By dropping perovskite precursor solution on flexible conductive glass and depositing top electrodes, the problem of restriction of RRAM's high-temperature crystallization process on flexible substrates is solved, and a high-quality perovskite variable-resistance memory on flexible wearable devices is realized Prepared for flexible wearable electronic devices.

CN119212547APending Publication Date: 2024-12-27HUBEI XINGCHEN TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411559871.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The application of existing RRAM in flexible wearable electronic devices is limited by the high-temperature crystallization process and poor oxygen resistance, and it is difficult to prepare high-quality perovskite resistance functional layers on flexible substrates.

Method used

The perovskite precursor solution was prepared by spin coating on the flexible conductive glass by using low boiling point solvent di-methoxyethanol, and the top electrode was deposited with vacuum evaporation, which eliminated the high-temperature annealing process and prepared the crystal phase transformation. A perovskite resistance functional layer with complete and well-crystallized film.

Benefits of technology

It has achieved the preparation of high-quality perovskite flexible resistive memory suitable for flexible wearable devices under the conditions of no high-temperature annealing in the entire air environment, which has enhanced its application potential on flexible substrates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119212547A_ABST
    Figure CN119212547A_ABST
Patent Text Reader

Abstract

The invention discloses a flexible resistive random access memory and a preparation method thereof, and relates to the technical field of solar cells, and the method comprises the steps: providing flexible conductive glass, and carrying out the pretreatment of the flexible conductive glass, so that the surface of the flexible conductive glass is clean; the method comprises the following steps: dissolving a mixed solute composed of PbI2, FAI, MAI and MACl in a mixed solvent composed of di-methoxyethanol, acetonitrile and NMP to obtain a perovskite precursor solution; in an inert gas environment, dropping a perovskite precursor solution onto the conductive surface of the pretreated flexible conductive glass, and uniformly smearing the perovskite precursor solution by adopting a spin coating method; the flexible conductive glass is placed in a glove box environment for standing, and an MAPbI (3-x) Clx film is obtained; and depositing a top electrode on the top of the MAPbI3-xClx thin film by adopting a vacuum evaporation method. According to the method, the low-boiling-point solvent is adopted, the high-temperature annealing technological process of conventional thin film crystallization is omitted, the perovskite resistive function layer which is complete in crystalline phase transformation and good in thin film crystallization is obtained, and therefore the perovskite flexible resistive random access memory based on the non-annealing technology is manufactured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solar cells, and in particular to a flexible resistive random access memory and a preparation method thereof. Background Art

[0002] At present, traditional Si-based computing systems are approaching their limits in terms of physical size. In order to break the barriers of the von Neumann architecture and Moore's Law in the field of semiconductor chips, resistive random access memory (RRAM) is quite competitive due to its advantages such as fast access, high storage density and low power consumption. At the same time, compared with dynamic random access memory (DRAM), which cannot save user data information after power failure, RRAM, as a non-volatile memory, can effectively protect customer data in various emergency situations. In addition, RRAM is also called a memristor, which is currently recognized by researchers as the fourth basic circuit element besides resistors, capacitors and inductors. There is no doubt that the development potential of RRAM in the field of integrated circuits is immeasurable.

[0003] It is reported that many semiconductor materials are widely used as the resistive switching functional layer of the typical "sandwich" (metal layer-intermediate layer-metal layer, MIM) structure RRAM, such as metal oxides, organic materials, sulfur-containing compounds and perovskites. However, the poor oxygen resistance of organic materials in oxygen and humidity environments, the complex preparation process of sulfur-containing compounds, and the high preparation temperature of metal oxides limit the application field of RRAM. With the continuous advancement of science and technology, electronic devices have also entered the era of flexible wearables. So far, the high-temperature crystallization of multiple categories of semiconductor thin film materials based on the RRAM intermediate layer has always been the main reason hindering its assembly of devices on flexible substrates (PET materials). Therefore, the preparation process of the resistive switching functional layer has always been an important part of promoting the development of flexible wearable devices. Summary of the invention

[0004] The purpose of the present invention is to provide a flexible resistive random access memory and a preparation method thereof. By adopting a low-boiling point solvent, the high-temperature annealing process of conventional thin film crystallization is omitted, and a perovskite resistive random access functional layer with complete crystal phase transition and good thin film crystallization is obtained. The perovskite flexible resistive random access memory based on the annealing-free process can be widely used in flexible wearable electronic devices.

[0005] The embodiment of the present invention is achieved as follows:

[0006] According to a first aspect of an embodiment of the present invention, a method for preparing a flexible resistive random access memory is provided, the method comprising:

[0007] Providing flexible conductive glass, and pre-treating the flexible conductive glass to make its surface clean;

[0008] Dissolving a mixed solute consisting of PbI2, FAI, MAI and MACl in a mixed solvent consisting of di-methoxyethanol, acetonitrile and NMP to obtain a perovskite precursor solution;

[0009] In an inert gas environment, dripping the perovskite precursor solution onto the conductive surface of the pretreated flexible conductive glass, and applying it evenly by spin coating;

[0010] The flexible conductive glass was placed in a glove box environment and allowed to stand to obtain MAPbI 3-x Cl x film;

[0011] The MAPbI 3-x Cl x A top electrode is deposited on top of the film.

[0012] As an practicable manner, providing the flexible conductive glass and pre-treating the flexible conductive glass to make its surface clean comprises:

[0013] Providing a flexible conductive glass having a conductive surface;

[0014] Ultrasonic cleaning the flexible conductive glass using washing powder, deionized water, acetone and ethanol in sequence for 20 to 40 minutes using an ultrasonic cleaning machine;

[0015] Blowing the flexible conductive glass dry with a nitrogen gun;

[0016] The flexible conductive glass is irradiated with ultraviolet light by a UV instrument.

[0017] As an practicable manner, after drying the flexible conductive glass by a nitrogen gun, the method further comprises:

[0018] Pasting insulating tape on the conductive surface of the flexible conductive glass to divide the electrode area and the non-electrode area;

[0019] The flexible conductive glass is ozone cleaned for 20 to 40 minutes using an ozone cleaning machine.

[0020] As an practicable manner, the process of dissolving a mixed solute consisting of PbI2, FAI, MAI and MACl in a mixed solvent consisting of di-methoxyethanol, acetonitrile and NMP to obtain a perovskite precursor solution comprises:

[0021] Weigh 440-480 mg PbI2, 100-140 mg FAI, 30-65 mg MAI and 5-15 mg MACl to form a mixed solute, and place the mixed solute in a transparent container equipped with a stirring magnet;

[0022] Measure 1 mL of a mixed solvent of dimethoxyethanol, acetonitrile and NMP in a volume ratio of 6:3:1, and add the mixed solvent into the transparent container accordingly;

[0023] The transparent container is placed in a magnetic stirrer and stirred at 40 to 60° C. for 2 to 3 hours;

[0024] The obtained perovskite precursor solution is filtered.

[0025] As an practicable manner, the filtering treatment of the obtained perovskite precursor solution includes:

[0026] The perovskite precursor solution was filtered through a syringe using a 0.15-0.25 μm filter.

[0027] As an practicable manner, in an inert gas environment, the perovskite precursor solution is dripped onto the conductive surface of the pretreated flexible conductive glass, and the perovskite precursor solution is evenly applied by spin coating, including:

[0028] In an inert gas environment, using a pipette to measure 70 to 90 μL of the perovskite precursor solution and drop it onto the conductive surface of the pretreated flexible conductive glass;

[0029] The coating is performed by a spin coating machine at 2750 to 3250 rpm and 2750 to 3250 rpm / s for 20 to 30 seconds.

[0030] As an practicable method, the flexible conductive glass is placed in a glove box environment and allowed to stand to obtain MAPbI 3-x Cl x Films include:

[0031] The flexible conductive glass was placed in a glove box environment and allowed to stand for 5 to 6 hours to obtain MAPbI 3-x Cl x film.

[0032] As an implementable manner, the material of the top electrode is aluminum or gold, and the thickness of the top electrode is 100-200 nm.

[0033] As an practicable manner, the inert gas is nitrogen or argon.

[0034] According to a second aspect of the embodiments of the present invention, a flexible resistive random access memory is provided, which is prepared by using the above-mentioned method for preparing the flexible resistive random access memory.

[0035] The beneficial effects of the embodiments of the present invention include:

[0036] The preparation method of the flexible resistive random access memory comprises: providing a flexible conductive glass, and pre-treating the flexible conductive glass to make its surface clean; dissolving a mixed solute consisting of PbI2, FAI, MAI and MACl in a mixed solvent consisting of di-methoxyethanol, acetonitrile and NMP to obtain a perovskite precursor solution; in an inert gas environment, dripping the perovskite precursor solution onto the conductive surface of the pre-treated flexible conductive glass, and using a spin coating method to evenly coat the surface; placing the flexible conductive glass in a glove box environment and letting it stand to obtain MAPbI 3-x Cl x Thin film; MAPbI 3-x Cl x The top electrode is deposited on the top of the film. Compared with the conventional thin film crystallization method in the prior art, the preparation method of the flexible resistive random access memory provided by the present application uses a low boiling point solvent (i.e., di-methoxyethanol), omitting the high temperature annealing process of conventional thin film crystallization, and obtains a perovskite resistive random access functional layer with complete crystal phase transformation and good thin film crystallization. The perovskite flexible resistive random access memory based on the annealing-free process can be widely used in flexible wearable electronic devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0038] Figure 1 One of the flow charts of the method for preparing the flexible resistive random access memory provided by the embodiment of the present invention;

[0039] Figure 2 A second flowchart of a method for preparing a flexible resistive random access memory provided by an embodiment of the present invention;

[0040] Figure 3 A third flowchart of a method for preparing a flexible resistive random access memory provided by an embodiment of the present invention;

[0041] Figure 4 A fourth flowchart of a method for preparing a flexible resistive random access memory provided by an embodiment of the present invention;

[0042] Figure 5 A schematic diagram of the structure of a flexible resistive random access memory provided by an embodiment of the present invention;

[0043] Figure 6 An XRD spectrum of the resistive switching functional layer provided in an embodiment of the present invention;

[0044] Figure 7 A scanning electron microscope image of the MHP film provided by an embodiment of the present invention;

[0045] Figure 8 An IV curve diagram of the flexible resistive random access memory provided by an embodiment of the present invention when in an unbent state;

[0046] Fig. 9 A durability test diagram of the flexible resistive random access memory provided by an embodiment of the present invention when in an unbent state;

[0047] Fig.10 A retention time test diagram of a flexible resistive random access memory provided by an embodiment of the present invention;

[0048] Fig.11 IV curve diagram of the flexible resistive random access memory provided by an embodiment of the present invention after being bent at different angles;

[0049] Fig.12 IV curve diagram of the flexible resistive random access memory provided by an embodiment of the present invention after being bent for different times.

[0050] Icon: 001-flexible conductive glass; 002-film; 003-top electrode. DETAILED DESCRIPTION

[0051] The embodiments set forth below represent information necessary to enable those skilled in the art to practice the embodiments, and illustrate the best mode for practicing the embodiments. After reading the following description with reference to the accompanying drawings, those skilled in the art will understand the concepts of the present disclosure, and will recognize the applications of these concepts not specifically proposed herein. It should be understood that these concepts and applications are within the scope of the present disclosure and the appended claims.

[0052] It should be understood that although the terms first, second, etc. can be used to describe various elements in this article, these elements should not be limited by these terms. These terms are only used to distinguish one element from another element. For example, without departing from the scope of the present disclosure, the first element may be referred to as the second element, and similarly, the second element may be referred to as the first element. As used herein, the term "and / or" includes any and all combinations of one or more of the associated listed items.

[0053] It should be understood that when an element (such as a layer, region or substrate) is referred to as "on another element" or "extending onto another element", it can be directly on another element or directly extended onto another element, or there can also be an intervening element. On the contrary, when an element is referred to as "directly on another element" or "directly extending onto another element", there is no intervening element. Similarly, it should be understood that when an element (such as a layer, region or substrate) is referred to as "on another element" or "extending onto another element", it can be directly on another element or directly extended onto another element, or there can also be an intervening element. On the contrary, when an element is referred to as "directly on another element" or "extending directly onto another element", there is no intervening element. It should also be understood that when an element is referred to as "connected" or "coupled" to another element, it can be directly connected or coupled to another element, or there can be an intervening element. On the contrary, when an element is referred to as "directly connected" or "directly coupled" to another element, there is no intervening element.

[0054] Relative terms such as “below” or “above” or “upper” or “lower” or “horizontal” or “vertical” may be used herein to describe the relationship of one element, layer or region to another element, layer or region as shown in the figures.

[0055] The terms used herein are only used for the purpose of describing specific embodiments and are not intended to limit the present disclosure. As used herein, unless the context clearly indicates otherwise, the singular forms "a", "an", and "the" are intended to include the plural forms as well. It should also be understood that when used herein, the term "comprising" indicates the presence of the features, integers, steps, operations, elements, and / or parts, but does not exclude the presence or addition of one or more other features, integers, steps, operations, elements, parts, and / or groups of the above.

[0056] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as those commonly understood by those skilled in the art to which the present disclosure belongs. It should also be understood that the terms used herein should be interpreted as having the same meaning as they do in the context of this specification and the relevant art, and should not be interpreted in an idealized or overly formal sense, unless clearly defined in this article.

[0057] In recent years, metal halide perovskite (MHP) has attracted great attention due to its advantages such as low-temperature preparation, fast photoelectric response and low power consumption, making MHP-based electronic devices easier and more economical to manufacture than traditional silicon-based devices. Currently, MHP materials are widely used in solar cells, photodetectors, LEDs and other technical fields. In order to break the shackles of RRAM in flexible wearable electronic devices, please refer to Figures 1 to 12 The present application provides a flexible resistive random access memory and a preparation method thereof, wherein an MHP material is used as a resistive random access functional layer of an RRAM, and an MHP film 002 is prepared on a flexible substrate (PET / ITO) by an extremely simple one-step method in a full air environment and without a high temperature annealing process during the entire preparation process, and an aluminum (Al) electrode is used to assemble a PET / ITO / MAPbI 3-x Cl x Finally, the thin film 002 plane morphology and crystallinity of the semiconductor functional layer were characterized, and the IV characteristics, durability, retention time, different bending angles and different bending times of the device were further tested to verify the reliability of the flexible RRAM device.

[0058] Specifically, Figure 1 As shown, in a first aspect of an embodiment of the present application, a method for preparing a flexible resistive random access memory is provided, the method comprising:

[0059] S100, providing a flexible conductive glass 001, and pre-treating the flexible conductive glass 001 to make its surface clean;

[0060] S200, dissolving a mixed solute consisting of PbI2, FAI, MAI and MACl in a mixed solvent consisting of di-methoxyethanol, acetonitrile and NMP to obtain a perovskite precursor solution;

[0061] S300, in an inert gas environment, dripping a perovskite precursor solution onto the conductive surface of the pretreated flexible conductive glass 001, and applying the solution evenly by spin coating;

[0062] S400, placing the flexible conductive glass 001 in a glove box environment and letting it stand to obtain MAPbI 3-x Cl x film002;

[0063] S500, vacuum evaporation method in MAPbI 3-x Cl x A top electrode 003 is deposited on top of the thin film 002 .

[0064] It should be noted that, first, a flexible conductive glass 001 with a conductive surface is provided as a substrate, and the flexible conductive glass 001 is pretreated to make its surface clean and have good adhesion, so as to facilitate spin coating of the precursor solution on the conductive surface of the flexible conductive glass 001; secondly, a precursor solution is prepared, specifically, PbI2, FAI, MAI and MACl are selected as solutes, and di-methoxyethanol, acetonitrile and NMP are selected as solvents, and the above four solutes are all dissolved in the mixed solvent by continuous stirring. in an environment filled with inert gas, the prepared perovskite precursor solution is dripped onto the conductive surface of the pretreated flexible conductive glass 001, and the perovskite precursor solution is evenly coated on the conductive surface of the flexible conductive glass 001 by a spin coating method; then, the flexible conductive glass 001 coated with the perovskite precursor solution is placed in a glove box environment and allowed to stand, so that the perovskite precursor solution is gradually dried, thereby obtaining MAPbI 3-x Cl x Film 002; Finally, vacuum evaporation was used to deposit MAPbI 3-x Cl x Metal is deposited on the top of the film 002 as the top electrode 003, so that a perovskite flexible resistive random access memory can be prepared.

[0065] The preparation method of the flexible resistive random access memory provided in the present application omits the high-temperature annealing process of conventional thin film crystallization by adopting a low-boiling point solvent (i.e., dimethoxyethanol), thereby obtaining a perovskite resistive random access functional layer with complete crystal phase transition and good crystallization of the thin film 002. The perovskite flexible resistive random access memory based on the annealing-free process thus obtained can be widely used in flexible wearable electronic devices.

[0066] As an implementable approach, Figure 2 As shown, S110, providing a flexible conductive glass 001, and pre-treating the flexible conductive glass 001 to make its surface clean includes:

[0067] S110, providing a flexible conductive glass 001 having a conductive surface;

[0068] S120, ultrasonically cleaning the flexible conductive glass 001 using washing powder, deionized water, acetone and ethanol in sequence for 20 to 40 minutes using an ultrasonic cleaning machine;

[0069] S130, drying the flexible conductive glass 001 by a nitrogen gun;

[0070] S160. Expose the flexible conductive glass 001 to ultraviolet light using a UV instrument.

[0071] It should be noted that in the actual production process, the pretreatment of the flexible conductive glass 001 can be achieved through the following steps. First, the flexible conductive glass 001 is ultrasonically cleaned by an ultrasonic cleaning machine, using detergent powder, deionized water, acetone and ethanol in turn, each cleaning for 20 to 40 minutes to make the surface of the flexible conductive glass 001 clean; secondly, the flexible conductive glass 001 is blown dry by a nitrogen gun to make the surface of the flexible conductive glass 001 dry; thirdly, the flexible conductive glass 001 is irradiated with ultraviolet light by a UV instrument to excite the conductive particles in the flexible conductive glass 001, so that electrons can pass through more easily, thereby enhancing the conductive properties of the flexible conductive glass 001.

[0072] Further, as an implementable method, Figure 2 As shown, S130, after the flexible conductive glass 001 is dried by a nitrogen gun, the method further includes:

[0073] S140, sticking an insulating tape on the conductive surface of the flexible conductive glass 001 to divide the electrode area and the non-electrode area;

[0074] S150, ozone cleaning the flexible conductive glass 001 for 20 to 40 minutes using an ozone cleaning machine.

[0075] It should be noted that, in the actual production process, in addition to the above steps, after the flexible conductive glass 001 is blown dry by a nitrogen gun, an insulating tape can be pasted on the edge of the conductive surface of the flexible conductive glass 001 to divide the electrode area and the non-electrode area, so as to facilitate the deposition of the top electrode 003 at the position of the corresponding electrode area in the subsequent steps; because the pasting of the insulating tape may cause contamination to the flexible conductive glass 001, the flexible conductive glass 001 can be ozone cleaned for 20 to 40 minutes by an ozone cleaning machine.

[0076] As an implementable approach, Figure 3 As shown, S200, a mixed solute consisting of PbI2, FAI, MAI and MACl is dissolved in a mixed solvent consisting of di-methoxyethanol, acetonitrile and NMP to obtain a perovskite precursor solution comprising:

[0077] S210, weigh 440-480 mg PbI2, 100-140 mg FAI, 30-65 mg MAI and 5-15 mg MACl to form a mixed solute, and place the mixed solute in a transparent container equipped with a stirring magnet;

[0078] S220, measuring 1 mL of a mixed solvent of dimethoxyethanol, acetonitrile and NMP in a volume ratio of 6:3:1, and adding the mixed solvent into a transparent container;

[0079] S230, placing the transparent container in a magnetic stirrer and stirring at 40-60° C. for 2-3 hours;

[0080] S240, filtering the obtained perovskite precursor solution.

[0081] It should be noted that in the actual production process, dimethoxyethanol, acetonitrile and NMP with a volume ratio of 6:3:1 are measured to form a mixed solvent, and 440-480 mg PbI2, 100-140 mg FAI, 30-65 mg MAI and 5-15 mg MACl solute powders are added to each 1 mL of the mixed solvent to prepare a mixed solution. The transparent container containing the mixed solution can be placed in a magnetic stirrer and stirred at 40-60°C for 2-3 hours to ensure complete mixing, thereby obtaining a perovskite precursor solution; on this basis, the perovskite precursor solution can also be filtered to further ensure that there are fewer impurities in the solution, the solution is clearer, and there are fewer impurities after crystallization.

[0082] In a preferred embodiment, 461 mg PbI2, 120.4 mg FAI, 47.7 mg MAI and 10.1 mg MACl can be weighed to form a mixed solute, and dimethoxyethanol, acetonitrile and NMP with a volume ratio of 6:3:1 are measured to form 1 mL of a mixed solvent to prepare a mixed solution. The specific calculation basis is: based on 1 mmol of PbI2, MAI:FAI=3:7, and the addition amount of MACl is 15%. The specific calculation rules for each component are: 1 mmol PbI2=461 mg, FAI=172*0.001*0.7=120.4 mg, MAI=159*0.001*0.3=47.7 mg, MACl=67.5*0.001*0.15=10.1 mg.

[0083] For example, as an implementable method, Figure 3 As shown, S240, filtering the obtained perovskite precursor solution includes: S241, filtering the perovskite precursor solution through a syringe using a 0.15-0.25 μm filter head. Regarding the actual size of the filter head, those skilled in the art should be able to reasonably select and design it according to actual conditions, and no specific limitation is made here.

[0084] As an implementable approach, Figure 4 As shown, S300, in an inert gas environment, dripping a perovskite precursor solution onto the conductive surface of the pretreated flexible conductive glass 001, and applying the solution evenly by a spin coating method, including:

[0085] S310, in an inert gas environment, using a pipette to measure 70 to 90 μL of a perovskite precursor solution and drop it onto the conductive surface of the pretreated flexible conductive glass 001;

[0086] S320, use a coating machine to use a spin coating method at 2750-3250 rpm, 2750-3250 rpm / s for 20-30 seconds.

[0087] It should be noted that in the actual production process, in an environment filled with inert gas, a certain amount of perovskite precursor solution is measured with a pipette and dropped onto the conductive surface of the pretreated flexible conductive glass 001. The perovskite precursor solution is evenly applied to the conductive surface of the flexible conductive glass 001 by spin coating at 2750-3250 rpm and 2750-3250 rpm / s for 20-30 seconds. The amount of perovskite precursor solution can be adjusted by a person skilled in the art according to the area of ​​the conductive surface of the flexible conductive glass 001 and the desired MAPbI 3-x Cl x The thickness of the film 002 is designed and is not specifically limited here.

[0088] As an practicable method, S400, the flexible conductive glass 001 is placed in a glove box environment and allowed to stand to obtain MAPbI 3-x Cl x Film 002 includes:

[0089] S410, placing the flexible conductive glass 001 in a glove box environment and leaving it to stand for 5 to 6 hours, so that the perovskite precursor solution on the conductive surface gradually dries to form a film, thereby obtaining MAPbI 3-x Cl x Film 002.

[0090] As an implementable approach, Figure 5 As shown, the material of the top electrode 003 is aluminum or gold, and the thickness of the top electrode 003 is 100-200 nm. As an practicable manner, the inert gas is nitrogen or argon.

[0091] like Figure 6 As shown in the figure, the analysis of the crystal structure of the prepared MHP film 002 was completed using an X-ray diffractometer (XRD, D8FOCUS, θ=5-50°). The typical characteristic peaks of the MHP film 002 have been marked. In addition, the residual PbI2 impurity content in the perovskite crystal is very small, and the weak XRD peak of ITO-PET also shows that the uniformity of the coating of the film 002 is good.

[0092] like Figure 7As shown, a scanning electron microscope (SEM, JSM-7100F) was also used to observe the surface morphology of the samples. Figure 7 The crystal state of the grains of MHP film 002 at a SEM magnification size of 1 μm is shown. It can be seen that the perovskite film 002 grows densely and the grains have good crystallinity, which will also be beneficial to the stability of perovskite RRAM.

[0093] like Figures 8 to 12 As shown, the IV characteristics, durability, retention time and flexibility of the flexible resistive memory were tested in an air environment (relative humidity ≥ 50%, temperature about 25° C.) using a semiconductor tester B1500A.

[0094] like Figure 8 As shown, the IV curve of the flexible RRAM device in the unbent state after 100 cycles of operation is shown. The test was completed using the semiconductor tester B1500A. First, the metal Al electrode was connected to a negative scanning voltage, and the ITO electrode was connected to a positive scanning voltage. When the negative scanning voltage was 0 to -2V, the current value of the device increased sharply to 1mA at -0.3V to reach the current limit. This process indicates that the resistance value switches from a high resistance state (HRS) to a low resistance state (LRS), that is, the SET process; when the scanning voltage is from 0V to 2V, the current drops sharply within 1V, and this transition corresponds to the RESET process. The appearance of the SET and RESET processes indicates that the RRAM exhibits a bipolar resistive switching phenomenon.

[0095] like Fig. 9 As shown in the figure, the endurance of the flexible RRAM device in the unbent state after 100 cycles of operation is demonstrated. According to the high and low resistance state distribution diagram of the endurance, it can be seen that the storage window (ON / OFF ratio) of the memory is greater than 10 2 These results indicate that the perovskite flexible RRAM device based on the annealing-free process has objective electrical performance before bending.

[0096] like Fig.10 As shown in FIG. 1 , the retention time (Retention Time, read voltage Vread=0.2V) of the flexible RRAM device is shown. Fig.10 The results show that the retention time is > 8×10 3 s.

[0097] like Fig.11 As shown, the IV curves of the flexible RRAM device after bending at different angles (initial -15°-30°-60°-90°) are shown. Fig.12 As shown, the IV curve of the flexible RRAM device after bending for different times (initial-50-100-200times) is shown. Fig.11and Fig.12 The results show that the IV curve of the perovskite flexible RRAM device based on the annealing-free process has considerable consistency after bending.

[0098] According to a second aspect of the embodiments of the present application, a flexible resistive memory is provided. The flexible resistive memory is prepared by using the above-mentioned method for preparing a flexible resistive memory.

[0099] It should be noted that the specific structure of the flexible resistive memory provided in this embodiment is the same as the method for preparing the flexible resistive memory in the foregoing text. A person skilled in the art can infer the specific structure of the flexible resistive memory based on the description of the method for preparing the flexible resistive memory in the foregoing text, and this application will not repeat the description. Since the flexible resistive memory provided in this embodiment is prepared by adopting the method for preparing the flexible resistive memory, the flexible resistive memory has the same beneficial effects as the method for preparing the flexible resistive memory, and will not be described in detail here.

[0100] The above description is only an optional embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

[0101] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

Claims

1. A method for preparing a flexible resistive random access memory, characterized in that: The method comprises: Providing flexible conductive glass, and pre-treating the flexible conductive glass to make its surface clean; Dissolving a mixed solute consisting of PbI2, FAI, MAI and MACl in a mixed solvent consisting of di-methoxyethanol, acetonitrile and NMP to obtain a perovskite precursor solution; In an inert gas environment, dripping the perovskite precursor solution onto the conductive surface of the pretreated flexible conductive glass, and applying it evenly by spin coating; The flexible conductive glass was placed in a glove box environment and allowed to stand to obtain MAPbI 3-x Cl x film; The MAPbI 3-x Cl x A top electrode is deposited on top of the film.

2. The method for preparing a flexible resistive random access memory according to claim 1, characterized in that: The step of providing the flexible conductive glass and pre-treating the flexible conductive glass to make its surface clean comprises: Providing a flexible conductive glass having a conductive surface; Ultrasonic cleaning the flexible conductive glass using washing powder, deionized water, acetone and ethanol in sequence for 20 to 40 minutes using an ultrasonic cleaning machine; Blowing the flexible conductive glass dry with a nitrogen gun; The flexible conductive glass is irradiated with ultraviolet light by a UV instrument.

3. The method for preparing a flexible resistive random access memory according to claim 2, characterized in that: After drying the flexible conductive glass by a nitrogen gun, the method further comprises: Pasting insulating tape on the conductive surface of the flexible conductive glass to divide the electrode area and the non-electrode area; The flexible conductive glass is ozone cleaned for 20 to 40 minutes using an ozone cleaning machine.

4. The method for preparing a flexible resistive random access memory according to claim 1, characterized in that: The method of dissolving a mixed solute consisting of PbI2, FAI, MAI and MACl in a mixed solvent consisting of di-methoxyethanol, acetonitrile and NMP to obtain a perovskite precursor solution comprises: Weigh 440-480 mg PbI2, 100-140 mg FAI, 30-65 mg MAI and 5-15 mg MACl to form a mixed solute, and place the mixed solute in a transparent container equipped with a stirring magnet; Measure 1 mL of a mixed solvent of dimethoxyethanol, acetonitrile and NMP in a volume ratio of 6:3:1, and add the mixed solvent into the transparent container accordingly; The transparent container is placed in a magnetic stirrer and stirred at 40 to 60° C. for 2 to 3 hours; The obtained perovskite precursor solution is filtered.

5. The method for preparing a flexible resistive random access memory according to claim 4, characterized in that: The filtering treatment of the obtained perovskite precursor solution comprises: The perovskite precursor solution was filtered through a syringe using a 0.15-0.25 μm filter.

6. The method for preparing a flexible resistive random access memory according to claim 1, characterized in that: The step of dripping the perovskite precursor solution onto the pretreated conductive surface of the flexible conductive glass in an inert gas environment and applying the solution evenly by spin coating comprises: In an inert gas environment, using a pipette to measure 70 to 90 μL of the perovskite precursor solution and drop it onto the conductive surface of the pretreated flexible conductive glass; The coating is performed by a spin coating machine at 2750 to 3250 rpm and 2750 to 3250 rpm / s for 20 to 30 seconds.

7. The method for preparing a flexible resistive random access memory according to claim 1, characterized in that: The flexible conductive glass is placed in a glove box environment and allowed to stand to obtain MAPbI 3-x Cl x Films include: The flexible conductive glass was placed in a glove box environment and allowed to stand for 5 to 6 hours to obtain MAPbI 3-x Cl x film.

8. The method for preparing a flexible resistive random access memory according to claim 1, characterized in that: The material of the top electrode is aluminum or gold, and the thickness of the top electrode is 100-200 nm.

9. The method for preparing a flexible resistive random access memory according to claim 1, characterized in that: The inert gas is nitrogen or argon.

10. A flexible resistive random access memory, characterized in that: The flexible resistive random access memory is prepared by the method for preparing the flexible resistive random access memory according to any one of claims 1 to 9.